Infant attachment predicts bodily freezing in adolescence: evidence from a prospective longitudinal study - Niermann, Hannah C. M.; Ly, Verena; Smeekens, Sanny; Figner, Bernd; Riksen-Walraven, J. Marianne; Roelofs, Karin (Frontiers in Behavioral Neuroscience, 2015)
Early life-stress, particularly maternal deprivation, is associated with long-lasting deviations in animals’ freezing responses. Given the relevance of freezing for stress-coping, translational research is needed to examine the relation between insecure infant-parent attachment and bodily freezing-like behavior in humans. Therefore, we investigated threat-related reductions in body sway (indicative of freezing-like behavior) in 14-year-old adolescents (N=79), for whom attachment security was earlier assessed in infancy. As expected, insecure (versus secure) attachment was associated with less body sway for angry versus neutral faces. This effect remained when controlling for intermediate life-events. These results suggest that the long-lasting effects of early negative caregiving experiences on the human stress and threat systems extend to the primary defensive reaction of freezing. Additionally, we replicated earlier work in adults, by observing a significant correlation (in adolescents assessed as securely attached) between subjective state anxiety and reduced body sway in response to angry versus neutral faces. Together, this research opens venues to start exploring the role of freezing in the development of human psychopathology.